Creativity: Studying the identity of processed meat packaging for retail entrepreneurs in Thailand - Sarunpong Akkaratananpong; Thanate Piromgarn; Sirisyos Kijmongkolvanich; Songwut Egwutvongsa (Edelweiss Applied Science and Technology, 2024)
The aim of this research was to compare the newly developed processed meat packaging in Thailand’s retail market and to study the factors affecting consumer purchasing decisions. In this study, a mixed methods approach was applied using a structured questionnaire, in which the alpha coefficient was good (0.903), as the research tool. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) and AMOS programs. The packaging comparison results showed that consumers’ satisfaction with the newly developed processed meat packaging led to increased satisfaction. In addition, three factors affecting the new packaging design were identified, which is consistent with the empirical data, and showed discriminant validity that could be applied to separate the factors used to evaluate the customers’ feelings in the retail market. The results also indicated that shelf life extension, product differentiation, and convenience of portability were the vital components affecting consumer purchasing decisions. Thus, entrepreneurs can adapt these three factors to the marketing strategies development of their processed meat packaging in order to maximize the distribution opportunities for their sustainable economic stability in Thailand’s retail market.
Keywords: Consumer Packaging Perceptions and Trends; Digital Media and Visual Art